2017
DOI: 10.1111/nmo.13088
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety can significantly explain bolus perception in the context of hypotensive esophageal motility: Results of a large multicenter study in asymptomatic individuals

Abstract: Background: Previous studies have not been able to correlate manometry findings with bolus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
(84 reference statements)
0
11
2
2
Order By: Relevance
“…The clinical significance of IEM remains unclear because most studies failed to find any correlation with symptoms 2‐6,9,19 . In the study by Jain et.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of IEM remains unclear because most studies failed to find any correlation with symptoms 2‐6,9,19 . In the study by Jain et.…”
Section: Discussionmentioning
confidence: 99%
“…bolus transit perception in patients without mechanical obstruction might be due to esophageal hypersensitivity (7) . Anxiety is a predictor of perception of esophageal bolus transit in cases of hypotensive motility (15) . Esophageal motor function alone did not explain differences in bolus perception, suggesting that different mechanisms are relevant in different individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Esophageal motor function alone did not explain differences in bolus perception, suggesting that different mechanisms are relevant in different individuals. The perception of bolus transit is less common than abnormal motility (15) . In a previous investigation only 9.6% of the volunteers reported perception of esophageal bolus passage, which happened in 3.5% of the swallows (15) .…”
Section: Resultsmentioning
confidence: 99%
“…Carlson et al found no difference in responder rate (defined as ESS < 3) when comparing patients with complete vs incomplete bolus transit after treatment. This lack of correlation between bolus perception/dysphagia and objective measurements has also been shown using other ways of sensation evaluation (like Likert scale) in healthy and symptomatic individuals . This highlights the fact that dysphagia is a complex phenomenon that goes far beyond our current methods to evaluate esophageal function.…”
Section: Discussionmentioning
confidence: 99%